The Identification Of Self-Assessment To Develop Students’ Writing Skill - Deviana Elwis Simarmata; Tarigan, Karisma Erikson; Prayuda, Meikardo Samuel (Journal of English Language Learning, 2023)
Many students still didn’t understand how to write properly and correctly, there are also many obstacles’ students face when writing, one of which is how to arrange sentences in making stories, and many don't know that writing is also one of the 4 abilities that are often used by many people. The writer brought this self-assessment method to the SMP Santo Petrus Medan to be used as research material for students. The purpose of this method is for students to know what obstacles make students late in understanding how to write well. After the self-assessment method was taught in class which would be used as research material by the writer, the writer found that in the final test students almost all students understood what the self-assessment method was, and in the description of the data it can be seen that the number of students in the experimental class was 27 students and in the control class as many as 27 students. From the experimental class scores, the average pre-test was 62.70 and the post-test was 79.70. The median for the pre-test was 62.00 and for the post-test was 80.00. The lowest score for the pre-test was 50 and the highest was 76. For the post-test, 70 was obtained for the lowest score and 90 for the highest score. It can be concluded that the lowest and highest scores on the post-test are higher than the pre-test.